(untitled) (REMUNOM, 2026)
Pineapple is a widely consumed fruit in Brazil and holds strong agricultural relevance, especially in the North and Northeast regions, with Pará standing out in national production. The wide availability of the fruit favors the market for industrialized pulps, products that are increasingly present in daily diets. In this context, the study aimed to evaluate the physical, physicochemical, and chemometric characteristics of different brands of industrialized pulps of Ananas comosus L. produced in Pará. Parameters such as pH, density, moisture, electrical conductivity, total soluble solids, titratable acidity, and ratio were analyzed, in addition to applying chemometric analyses to better interpret the data obtained. The results showed relevant differences among the evaluated brands, especially regarding soluble solids, acidity, and electrical conductivity, parameters directly related to fruit ripening, composition, and processing. Multivariate analyses allowed the formation of distinct groupings among the brands, revealing specific patterns and significant differences in the chemical profile of each product. It was concluded that there is important variability among the industrialized pulps analyzed and that the combined use of physicochemical and chemometric methods is effective for assessing quality and guiding improvements in the production process.